Dicyanovinyl-quinquethiophenes with varying alkyl chain lengths: Investigation of their performance in organic devices - Schulze, K; Riede, M; Brier, E; Reinold, E; Bäuerle, P; Leo, K (American Institute of Physics, 2008)
We compare between two derivatives of dicyanovinyl-quinquethiophenes with different alkyl side chain lengths. Both materials show comparable open circuit voltages Voc in organic solar cells with fullerene C60 as acceptor, as expected since they have the same highest occupied molecular orbital energy. However, differences in the current-voltage-characteristics, particularly in the fill factor, are observed. We analyze both derivatives in hole-only devices and find a difference in the hole injection between the doped hole transport layer and the oligothiophenes. Additionally, we determine the hole mobility of the two materials and explain the different behaviors of the two materials in solar cells. © 2008 American Institute of Physics.